Formate production from CO2 electroreduction in a salinity-gradient energy intensified microbial electrochemical system. (January 2021) - Tian, Yan; Li, Da; Liu, Guohong; Li, Chao; Liu, Jia; Wu, Jing; Liu, Junfeng; Feng, Yujie
Graphical abstract: Highlights: CO2 reduction was self-driven in microbial reverse electrodialysis cell. Formate production and wastewater treatment could be achieved simultaneously. The formate concentration could reach 143.5 ± 8.1 mg L −1 with COD removal over 80%. The stability of system depended on the provision of electron donors. Abstract: The electricity production of microbial electrochemical system can be substantially strengthened by coupling with a reverse electrodialysis stack which extracts energy from salinity gradient, therefore provides a possible way for value-added products in cathode without external energy input. Here, a microbial reverse-electrodialysis CO2 reduction cell (MRECC) was developed and successfully utilized to drive CO2 -to-formate conversion on a Bi/Cu cathode. Results confirmed the optimal anodic COD load and cathodic CO2 flow rate to be 1 g NaAc L −1 and 10 mL min −1 . MRECC could yielded 143.5 ± 8.1 mg L −1 of formate with total energy efficiency of 4.6 ± 0.9% and coulombic efficiency of 46.4 ± 2.4%. Increasing or decreasing anode or cathode load impaired MRECC performance from economic and environmental viabilities. MRECC provided a promising platform for simultaneous CO2 reduction and value-added chemicals production by using sustainable energy from wastewaters.